ISLAM DI KALIMANTAN SELATAN DILIHAT DARI PERSPEKTIF POLITIK DAN PEMERINTAHAN - ., Nor Wahidah (Pascasarjana UIN ANTASARI Banjarmasin, 2009)
To understand the Islam in South Borneo through politics and government aspect must be started from the beginning of Banjar Kingdom as the first islamic kingdom in South Borneo. The Banjar kingdom found by Raden Samudera titled Sultan Suriansyah in the couple of 1525 M. The leader of Banjar Kingdom put Islam as the state official religion. In 1860 M, the Banjar kingdom was dismissed by the collonial dutch government. Since that time, the muslim people in south Borneo had no rule in politic and government. When Indonesia declared his independence and did the general election in 1955s, the political aspiration of muslim people given to Nadhatul Ulama and Masyumi while the next general election (1971-1997), the votes of Islamic party decreased slowly.